On Generalized Bell Polynomials - Roberto B. Corcino; Cristina B. Corcino (Discrete Dynamics in Nature and Society)
It is shown that the sequence of the generalized Bell polynomials Sn(x) is convex under some restrictions of the parameters involved. A kind of recurrence relation for Sn(x) is established, and some numbers related to the generalized Bell numbers and their properties are investigated.